FTX271: A potential gene resource for plant antiviral transgenic breeding - Zhang, Yuhan; Gao, Chaoming; Zhang, Yahong; Huang, Hang; Du, Yameng; Wu, Lan; Wu, Liping (Frontiers in Microbiology, 2022)
Flammutoxin (FTX), as well as its precursor TDP, are proteins from Flammulina velutipes with antiviral activity. Transgenic tobacco with the FTX271 (gene of FTX or TDP) can not only delay the onset time of symptoms but also alleviate the symptoms caused by tobacco mosaic virus (TMV), but the mechanism is still unclear. In this study, FTX271 was introduced into Nicotiana benthamiana, and the disease resistance mechanism activated by FTX271 was speculated by transcriptomic and proteomic techniques. The results showed that TDP was detected, and some genes, proteins and pathways were significant upregulated or enriched in transgenic tobacco, including the mitogen-activated protein kinase (MAPK) cascade signal transduction pathway, the expression of hypersensitive response (HR) marker genes H1N1 and HSR203J, pathogenesis-related (PR) genes, and the key genes COI1 and lipoxygenase gene LOX2 of the jasmonic acid (JA) signaling pathway, indicating FTX271 may activate the MAPK pathway and increase the content of reactive oxygen species (ROS) and JA, which promoted the HR and inducible systemic resistance (ISR). ISR caused increased expression of peroxidase (POD) and other proteins involved in pathogen defense. In addition, transgenic tobacco may use sHSP-assisted photoreparation to alleviate the symptoms of TMV. In conclusion, JA-mediated ISR and sHSP-assisted photoreparation are activated by FTX271 to protect tobacco from TMV infection and alleviate the symptoms caused by the virus. The study provided a theoretical basis for the TMV resistance mechanism of FTX271, which may represent a potential gene resource for plant antiviral transgenic breeding.